Implications of hydropower variability from climate change for a future, highly-renewable electric grid in California. (1st March 2019) - Tarroja, Brian; Forrest, Kate; Chiang, Felicia; AghaKouchak, Amir; Samuelsen, Scott
Highlights: Climate-induced variability in hydropower can increase greenhouse gas emissions. Higher dispatchable capacity needed to compensate for hydropower variability. Hydropower under climate change has minimal effects on renewable penetration. Higher hydropower variability increases natural gas power plant start up events. Climate-induced hydropower variability increases natural gas power plant downtime. Abstract: This study investigates how hydropower generation under climate change affects the ability of the electric grid to integrate high wind and solar capacities. Using California as an example, water reservoir releases are modeled as a function of hydrologic conditions in the context of a highly-renewable electric grid in the year 2050. The system is perturbed using different climate models under the Representative Concentration Pathway 8.5 climate scenario. The findings reveal that climate change impact on hydropower can increase greenhouse gas emissions up to 8.1% due to increased spillage of reservoir inflow reducing hydropower generation, but with minimal effects (<1%) on renewable utilization and levelized cost of electricity. However, increases in dispatchable power plant capacity of +2.1 to +6.3% and decreases in the number of start-up events per power plant unit up to 3.1%, indicate that the majority of dispatchable natural gas power plant capacity is offline for most of the climate change scenarios. While system-wide performance metrics experience small impacts, climate change effects on hydropower generation increase both the need for dispatchable generation and the costs of electricity from these power plants to support large-scale wind and solar integration on the electric grid.